Identifikasi Permasalahan Sarana dan Prasarana Di Sekolah-Sekolah Daerah Yang Tidak Memenuhi Standar Nasional Pendidikan (SNP) - Gabriella Sonia (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
Educational facilities and infrastructure are essential elements in creating a safe and effective learning environment. However, many schools in remote and 3T areas in Indonesia still have not met the minimum requirements of the National Education Standards (SNP). This study aims to identify the main problems of educational facilities and infrastructure and to formulate a strategic intervention model based on previous studies. This research used a qualitative descriptive approach through a Systematic Literature Review (SLR) with the PRISMA framework. Articles published between 2018 and 2025 were selected from Google Scholar and Scopus. The findings show five main problems: inadequate school buildings, limited classrooms, insufficient laboratories and libraries, limited access to electricity and internet, and poor sanitation. The proposed intervention model includes regional prioritization, multi-stakeholder collaboration, and digital-based monitoring to support more equitable and evidence-based educational policy.